MiR-150 in HTLV-1 infection and T-cell transformation - D’Agostino, Donna M.; Raimondi, Vittoria; Silic-Benussi, Micol; Ciminale, Vincenzo (Frontiers in Immunology, 2022)
Human T-cell leukemia virus-1 (HTLV-1) is a retrovirus that persistently infects CD4+ T-cells, and is the causative agent of adult T-cell leukemia/lymphoma (ATLL), tropical spastic paraparesis/HTLV-1-associated myelopathy (TSP/HAM) and several inflammatory diseases. T-cell transformation by HTLV-1 is driven by multiple interactions between viral regulatory proteins and host cell pathways that govern cell proliferation and survival. Studies performed over the last decade have revealed alterations in the expression of many microRNAs in HTLV-1-infected cells and ATLL cells, and have identified several microRNA targets with roles in the viral life cycle and host cell turnover. This review centers on miR-150-5p, a microRNA whose expression is temporally regulated during lymphocyte development and altered in several hematological malignancies. The levels of miR-150-5p are reduced in many HTLV-1-transformed- and ATLL-derived cell lines. Experiments in these cell lines showed that downregulation of miR-150-5p results in activation of the transcription factor STAT1, which is a direct target of the miRNA. However, data on miR-150-5p levels in freshly isolated ATLL samples are suggestive of its upregulation compared to controls. These apparently puzzling findings highlight the need for more in-depth studies of the role of miR-150-5p in HTLV-1 infection and pathogenesis based on knowledge of miR-150-5p-target mRNA interactions and mechanisms regulating its function in normal leukocytes and hematologic neoplasms.